Generating Functions for the Number of Permutations with Limited Displacement - Kløve, Torleiv (The Electronic Journal of Combinatorics, 2009)
Let V(d,n) be the number of permutations p of {1,2,… ,n} that satisfy |p_i-i|d for all i. Generating functions for V(d,n), for fixed d, are given.